Indigenuity : Native craftwork & the art of American literatures - Wigginton, Caroline (Critical indigeneities., 2022)
"In this innovative work at the intersection of Indigenous studies, literary studies, book history, and material culture studies, Caroline Wigginton tells a story of the interweavings of Native craftwork and American literatures from their ancient roots to the present. Focused primarily on North America, especially the colonized lands and waters now claimed by the United States, this book argues for the foundational but often-hidden aesthetic orientation of American literary history toward Native craftwork"--